Detecting Breast Cancer in X-RAY images using image segmentation algorithm and neural networks - Gdeeb, Rasha Talib (Informatica, 2023)
Breast cancer becomes is a nightmare threating woman all over the world, so, all the studies are trying for early detection of it to increase healing of it, it can save 30 percent from infected women which is a big percentage. Dangerous of breast cancer comes from the fact that all the women do not know about it until they have a mammogram image for the breast. It can be detected personally in late stages. That means it is important to make a medical examination periodically to investigate the presence of any cancerous lumps in breast tissue or underarm which can be an indicator for the existence of the tumour. Mammogram rays are an X-RAY applied on the breast which can used to find any problems in the breast like tumor blocks in breast, pain, secretions from nipples. Mammogram rays can detect breast cancer early and decrease the death cases. mammogram imaging starts in 40 age and must done every 3 years to assure the not infection of it. In cases of Genetic disease history, it is important to take the mammogram imaging before 40 age in the state of early tumor detection so it increases the recovery in early stages. This work is a study to create a method to estimate the breast cancer situation in X-RAY images to select an automatic medical solution which passes in three stages, primary aiding, chemical aiding, and eradication.